Morphology and distribution of the enigmatic Berkheya angusta (Asteraceae, Arctotideae) - Mckenzie, Robert J.; Karis, Per Ola; Gwynne-Evans, David (Phytotaxa, 2025)
Berkheya angusta is a woody, spinescent shrub currently classified as Vulnerable in the Red List of South African Plants. The species was described in 1899 by Rudolf Schlechter from a gathering at Elandskloof near Napier in the Western Cape province, South Africa, but was not encountered again for 110 years. The name has long been misapplied to superficially similar species of the closely related genus Cullumia, while plants of B. angusta have been misidentified as Cullumia species. Given this confusion, the paucity of information on its distribution and prevalence, and the need for reassessment of its conservation status, we here provide a full descriptive treatment of B. angusta and clarify its discrimination from morphologically similar species to ensure reliable identification. The species is known from a restricted area in the Overberg District of the Western Cape province. This study will enable a meaningful reappraisal of the conservation status of B. angusta, and will assist in improving the quality and rigour of future contributions of data on B. angusta to citizen science platforms, thereby expanding knowledge of the species.